2019
DOI: 10.1002/micr.30432
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular lining options for subtotal and total nasal reconstruction: A scoping review

Abstract: Background: Restoration of nasal lining is essential in reconstruction of subtotal/total nasal defects. When local flaps are inadequate, a microvascular flap should be used. The purpose of this scoping review is to map the literature and identify the described flap options for subtotal/total nasal reconstruction. Further to that, we will summarize the stated advantages and disadvantages, evaluate functional and esthetic outcomes, and appraise the current body of literature. Methods: An electronic literature se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…The ALT flap is the second most frequently used free flap for lining reconstruction, described in the 17% of the cases. 12 In our case series, lining reconstructions using ALT flap was comparable to RFF flap in term of number of treated patients, feasibility, surgical stages, functional and aesthetic outcomes, and complications.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The ALT flap is the second most frequently used free flap for lining reconstruction, described in the 17% of the cases. 12 In our case series, lining reconstructions using ALT flap was comparable to RFF flap in term of number of treated patients, feasibility, surgical stages, functional and aesthetic outcomes, and complications.…”
Section: Discussionmentioning
confidence: 52%
“…3 Ramji et al in a recent review found only few reports of microvascular lining reconstruction described in literature, with a total of 65 cases. 12 Afterward, Salibian et al published their 17-year experience in microvascular reconstruction of the nose with 47 patients. 8 In this article, we present our 19year experience in 21 consecutive patients, with full-thickness total/subtotal or heminasal defects, who underwent complex nasal reconstruction with microsurgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RFFF is the most common microvascular flap reported for nasal reconstruction (Menick & Salibian, 2011; Ramji et al, 2019; Marshall et al, 2003; Fujioka et al, 2012). Literature describes the use of other microvascular free flaps as a reliable option for lining reconstruction of total nasal defects (Ramji et al, 2019). Type of nasal defect and patient characteristics should be considered when choosing the reconstruction technique.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction implies reproducing the nasal aesthetic subunits (Burget & Menick, 1985, 1989) and the three nasal components: internal lining, osteochondral structure and external skin (Menick & Salibian, 2014; Menick, 2016). Different techniques have been described to treat total nasal defects (Brown & Shaw, 2010; Menick, 2010; Menick & Salibian, 2011; Brunetti et al, 2019; Ramji et al, 2019). This article reports a new custom design of the radial forearm free flap (RFFF) treating total nasal defects where the tip of the nose was preserved.…”
Section: Introductionmentioning
confidence: 99%